2018
DOI: 10.4049/jimmunol.1701670
|View full text |Cite
|
Sign up to set email alerts
|

eIF4E-Binding Proteins 1 and 2 Limit Macrophage Anti-Inflammatory Responses through Translational Repression of IL-10 and Cyclooxygenase-2

Abstract: Macrophages represent one of the first lines of defense during infections and are essential for resolution of inflammation following pathogen clearance. Rapid activation or suppression of protein synthesis via changes in translational efficiency allows cells of the immune system, including macrophages, to quickly respond to external triggers or cues without de novo mRNA synthesis. The translational repressors eIF4E-binding proteins 4E-BP1 and 4E-BP2 (4E-BP1/2) are central regulators of proinflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 72 publications
2
16
1
Order By: Relevance
“…Upon first consideration, these observations would seem inconsistent with our findings and those published in IFN‐γ‐stimulated 4E‐BP1 KO MEFs . However, these discrepancies could be attributed to specific translational programs triggered by different stimuli or stressors in immune versus nonimmune cells, as described by others and by us .…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Upon first consideration, these observations would seem inconsistent with our findings and those published in IFN‐γ‐stimulated 4E‐BP1 KO MEFs . However, these discrepancies could be attributed to specific translational programs triggered by different stimuli or stressors in immune versus nonimmune cells, as described by others and by us .…”
Section: Discussioncontrasting
confidence: 96%
“…Bioinformatic analysis of transcripts regulated via 4E‐BP1/2 in MΦs indicated that Ccl5 and Cxcl10 fall into the category of those that harbor relatively short 5′ UTRs (57 and 75 nt, respectively) with a minimum free energy (MFE) of –17.8 and –16.2 kcal/mol, respectively (Supporting Information ). Interestingly, Ccl5 and Cxcl10 share these features with Il1 a, Il1b , Il10 , Il12b , Ccl12 , and Cd40 . These similarities suggest a common mechanism of 4E‐BP1/2‐dependent selective translational control of immune‐related mRNAs in MΦs.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations